Indoor Location Estimation of Electromagnetically Shielded Chassis utilizing RSSI Fingerprint Pattern Matching - Yokoi, Toshiaki (IEEE/ION Position Location and Navigation Symposium, 2023)
Indoor location estimation is an important subject of research because it is useful for rescue assistance in times of dis-aster and for commercial applications in peacetime, like robot nav-igation in buildings. It accompanies difficulties to simulate the propagation of radio waves inside an elevator precisely, which has a narrow slit-like gap and an enclosure structure stacked with multiple metal plates. Therefore, it is necessary to clarify this by actual measurement. In this paper, I report the results of measuring RSSI in a consequently electromagnetically shielded environment, such as inside an elevator, and investigating the feasibility of its location estimation from RSSI inside the elevator enclosure. I measured the RSSI of an elevator with its doors closed and compared it to the RSSI outside the elevator to determine if it is possi-ble to estimate the location of the elevator enclosure. The target of this RSSI measurement is a reinforced concrete building with seven stories above ground and two below, and the total number of WLAN base stations is 101, using 2.4 GHz and 5 GHz frequency bands. First, all BSSID, frequency band, RSSI were measured with a smart phone at all 101 base station locations. Then, I meas-ured the RSSIs at inside of the elevator (with the doors closed) and outside the elevator, respectively. To ease the utilization of the RSSI fingerprint, I proposed the RSFI (Received signal strength indicator Fingerprint Similarity Index). The measurement results showed that the RSFI in the elevator on different floors are clearly different, indicating that position estimation is possible enough. Furthermore, RSFI was also found to indicates the differences in position within the elevator cabin. It is not difficult to use this RSFI, and I believe that it would be useful for the development of ILBS (Indoor Location Based Service) at the user level.